Penanaman Sikap Toleransi Anak Usia Dini dalam Buku Dongeng Binatang Penyelamat Penyu Belimbing - Marwany Marwany; Heru Kurniawan; Yuyun Ayu Lestari (Generasi Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2022)
The attitude of tolerance is one of the character education that must be instilled and applied in children. The task of parents and educators in providing understanding and example by planting from an early age. This study examines the book The Tale of the Animal Save the Leatherback Turtle by Titi Anisatul Laely and Mokhamad Nur Zaman from the aspect of tolerance for early childhood. Fairy tale books are one of the interesting media in instilling tolerance in early childhood. The purpose of this study was to analyze the inculcation of tolerance in early childhood in the book Tale of Animals to Save Leatherback Turtles by Titi Anisatul Laely and Mokhamad Nur Zaman. This type of research is descriptive qualitative with a textual analysis approach or library research in the form of literature review. The data source is from the book Fairy Tale of Animals to Save Leatherback Turtles by Titi Anisatul Laely and Mokhamad Nur Zaman. Data collection using documentation. Data analysis was carried out in several ways, namely data reduction, data classification, and verification of data information. The results of the study determine and identify that attitudes or behaviors that reflect the cultivation of an attitude of tolerance are mutual respect, help and accept differences (humble). These three attitudes are attitudes of tolerance that must be instilled from an early age in children, so that children can be accepted in a wider environment and can socialize with others.